TRINITY CHAPEL, CANTERBURY CATHEDRAL - Neal, David S.; Rodwell, Warwick (OXBOW BOOKS, 2022)
Illustrated analysis of a unique mosaic pavement in Canterbury Cathedral, fragments of an original shrine and the surrounding royal tombs.
Keywords: Thomas, -- à Becket, Saint, -- 1118?-1170 -- Death and burial.; Canterbury Cathedral -- History.; Thomas, -- à Becket, Saint, -- 1118?-1170; Canterbury Cathedral; Mosaic floors -- England -- Canterbury.; Religious architecture -- England -- Canterbury.; Planchers en mosaïque -- Angleterre -- Canterbury.; Architecture religieuse -- Angleterre -- Canterbury.; Mosaic floors; Religious architecture; England -- Canterbury; Electronic books.; History